PRAWNE GWARANCJE REALIZACJI ZASADY ROZDZIAŁU KOŚCIOŁA OD PAŃSTWA W XVII-WIECZNYM MARYLANDZIE - Michalik, Piotr (Zeszyty Prawnicze, 2016)
LEGAL GUARANTEES OF REALIZATION OF THE IDEA OF THE SEPARATION OF CHURCH AND STATE IN THE 17TH CENTURY MARYLAND Summary The paper is devoted to an analysis of church – state relations in the seventeenth century Maryland, an English colony founded in America in 1634 a Catholic, by Cecil Calvert, Lord Baltimore. As far as the paper concernes in seventeenth century Maryland there was not only religious toleration but also the separation of church and state. Although formally Charter of Maryland introduced Anglican establishment in the colony, lords Baltimore sought to realize the idea of the separation of church and state from the very beginning of the history of Maryland till the overthrow of Charles Calvert in 1689. Under the lords Baltimore the separation of church and state in Maryland was in practice guaranteed by several legislative acts enacted by Maryland General Assembly and sanctioned by Lord Baltimore, particularly An Act ordaining certain Laws for the Government of this Province from 1639, An Act for Church liberties from 1640 and An Act Concerning Religion from 1649.